The role of the government in the management of tourism object development of kurenai beach botubarani village, Kabila Bone Bone Bolango regency - Lucyane Djaafar; Nopiana Mozin (Institute of Computer Science (IOCS), 2022)
Tourism development in Indonesia is one of the catalysts in supporting regional development and is expected to be a sustainable economic support in accordance with the government's work plan. This clearly requires encouragement from the community as well as support from the government in an effort to create world-class tourism development. Based on the above, the purpose of this study examines about